Personal traits and competencies required to become successful students: A study among post diploma of Bachelor of Science in Information Studies / Nor Asma' Mohamad Nordin - Mohamad Nordin, Nor Asma' (Faculty of Information Management, 2010)
There has been much discussion about the competencies issues nowadays. Research regarding the influence of personal traits towards the achievement of college students' behavior and the examining of the competencies has primarily emphasized the importance of their spiritual quotient, emotional quotient, leadership, and competencies required such as attitudes, knowledge and skill. Those competencies are required in order to become successful students either in terms of academic or for the future. Through of all the competencies given, it is really hoped that the student has the ability in leading the new generation for one day. It is every employer or manager’s contention that for such an organization to be successful, all its employees must exercise personal responsibility and leadership. Therefore, in order to become successful students as well as successful librarian, they need to train themselves from now and have such of required competencies. Since the attended respondents of this research is focused on the post diploma students of Faculty of Information Management, Bachelor of Science in Information Studies, the researcher hope that those students are able to provide the information to the society and be a successful information provider. Their proficiency need to be accomplished in a successful way. Moreover, every society today needs the right information which has to be delivered on the right time and at the right places.